The Use of Indonesian/Malay Orthography in Tempo Doeloe Advertisement and Its Implication for Indonesian Learning - Sudaryanto Sudaryanto; Hermanto Hermanto (Universitas Tidar, 2018)
In terms of the history of its compilation, the Indonesian language has applied two of the four existing spellings, the Spelling van Ophuijsen and Spelling Suwandi or Spelling Republican. The Spelling of van Ophuijsen was coined by Charles Adriaan van Ophuijsen, a Dutch scholar of Malay, who compiled the book Kitab Logat Melajoe (1901). After Independence in 1945, the next two years, the Spelling Suwandi or Republican Spelling, based on Surat Keputusan No. 264/Bhg.A, date 19 March 1947, signed by Menteri Pengajaran, Pendidikan, dan Kebudayaan Mr. Soewandi. This research uses a qualitative-descriptive method. The data analyzed in the form of advertising tempo doeloe from the website www.wajibbaca.com. These advertisings, once analyzed, use a lot of Spelling van Ophuijsen and Spelling Suwandi or Spelling Republican. The result of this research is Spelling van Ophuijsen marked font oe, dj, and diacritic marks. Meanwhile, the Spelling of Suwandi has marked the font u substitute oe and the repeated word with number 2. Spelling in an advertisement can be used in lecture Indonesian (Bahasa Indonesia).